A 30-Year Journey Through Integrative Physiology Research and Education, Courtesy of Angiotensin II - Curtis, Kathleen S. (Frontiers in Physiology, 2021)
This brief article is a personal perspective on the importance of integrative physiology research and education, using angiotensin II as an example of how integrative physiology occurs and why it matters. It also offers suggestions and strategies to ensure that integrative physiology remains vibrant and appreciated.